Petal micromorphology and its relationship to pollination. (27th November 2016) - Costa, V. B. S.; Pimentel, R. M. M.; Chagas, M. G. S.; Alves, G. D.; Castro, C. C.
Abstract: The characteristics of petal epidermal conical cells affect the quality of the signals perceived by various pollinators. This study aimed to identify variations in micromorphological characteristics of flower petals and their relationship to melittophily, ornithophily and chiropterophily pollination systems. The petals of 11 species were analysed using scanning electron microscopy and optical microscopy and the micromorphological traits were described, measured and compared using Tukey's test, PCA and cluster analysis. Unlike chiropterophily, all melittophilous and some ornithophilous species possessed adaxial epidermal conical cells. Cluster grouping separated chiropterophilous flowers from melittophilous and ornithophilous. PCA analysis showed that the two morphometric profile of conical cells was the attribute that most strongly influenced the grouping of species. When considering the data set of the three pollination systems, melittophilous and ornithophilous plants were more similar to each other than they were to chriopterophilous species. The distance between conical cell apices is an important parameter in interactions with pollinators. This study facilitated recognition of smoothing pollinator resource access through petal micromorphological characteristics. Further research regarding the biometry of micromorphological traits related to pollination is required.